2020
DOI: 10.1109/trpms.2019.2930362
|View full text |Cite
|
Sign up to set email alerts
|

Compact Method for Proton Range Verification Based on Coaxial Prompt Gamma-Ray Monitoring: A Theoretical Study

Abstract: Range uncertainties in proton therapy hamper treatment precision. Prompt gamma-rays were suggested 16 years ago for real-time range verification, and have already shown promising results in clinical studies with collimated cameras. Simultaneously, alternative imaging concepts without collimation are investigated to reduce the footprint and price of current prototypes. In this manuscript, a compact range verification method is presented. It monitors prompt gamma-rays with a single scintillation detector positio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 79 publications
0
5
0
Order By: Relevance
“…27 Furthermore, the obtained result is in agreement with the reported analytical estimation in the literature as the number of emitted PGs, which partially contribute to the background, are linearly proportional to the beam range. 59 In our study, the background was defined as scattered and penetrated gammas produced already with primary PGs and neutrons during irradiation. We did not consider treatment room, couch, and beam nozzle.…”
Section: Discussionmentioning
confidence: 99%
“…27 Furthermore, the obtained result is in agreement with the reported analytical estimation in the literature as the number of emitted PGs, which partially contribute to the background, are linearly proportional to the beam range. 59 In our study, the background was defined as scattered and penetrated gammas produced already with primary PGs and neutrons during irradiation. We did not consider treatment room, couch, and beam nozzle.…”
Section: Discussionmentioning
confidence: 99%
“…by in-beam PET [10], and prompt gamma rays (PGs), e.g. by the prompt-gamma imaging [11], spectroscopy [12], timing [13] and peak-integration [14] methods. It has also been shown that the spatial distribution of fast neutrons (FNs) generated during treatment delivery is correlated to the proton range, and could reveal complementary information to PGs about the proton range [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Some imaging devices have been proposed in the past to monitor the proton range in vivo , which are modified versions of classical nuclear medicine imaging modalities 4 10 , while other more original approaches do not provide the full PG profile (e.g. prompt gamma spectroscopy 11 , PG integral counts 12 , 13 ). The existing methods have been extensively described in multiple reviews 3 , 14 , 15 .…”
Section: Introductionmentioning
confidence: 99%